Banana (Musa × Paradisiaca) Corm as an Alternative Substrate for Nata by Acetobacter xylinum - M. Ainul Mahbubillah; Fatma Atiq Khoridah; Muhammad Badrut Tamam; Fatan Mujahid (Food ScienTech Journal, 2025)
Banana corms, an underutilized by-product of banana (Musa × paradisiaca) cultivation, were investigated as a novel substrate for nata production using Acetobacter xylinum fermentation. This study evaluated the effects of varying sucrose concentrations (5%, 10%, and 15%), ammonium sulfate levels (0.5%, 1%, and 1.5%), and pH (3.5, 4, and 4.5) on nata thickness, wet weight, dry weight, water holding capacity (WHC), and organoleptic properties. The highest nata thickness (6.44 mm) and wet weight were observed in S3, A3, P3 (15% sucrose, 1.5% ammonium sulfate, pH 4.5). The highest dry weight was also obtained under these conditions. WHC varied between 6.50% and 17.00%, with S3, A2, P2 (15.00%) and S2, A3, P1 (16.00%) showing the highest values. Organoleptic analysis indicated that banana corm nata had a murky colour, slightly chewy texture, and sour taste, comparable to nata de coco but differing in acidity. The findings confirm that banana corms are a viable substrate for nata production, providing an innovative and sustainable approach to agricultural waste utilization with potential industrial applications.